Evaluating management zones and crop‐sensing relationships for improved irrigated maize nitrogen management. Issue 1 (28th February 2023) - Crowther, Joel; Parrish, John; Luck, Joe D.; Ferguson, Richard B.
Abstract: Active crop canopy sensors and management zones (MZ) are two methods of directing variable‐rate, in‐season nitrogen (N) fertilizer applications in maize ( Zea mays L.). Researchers have suggested that integrating these two approaches may result in improved performance of sensor‐based N application algorithms through increased N use efficiency and profitability. The objectives of this research study were to (1) identify soil and topographic variables that are related to in‐season canopy reflectance and yield for soil‐based MZ delineation and (2) determine if delineated MZ can identify areas with differential crop response to N fertilizer. N ramp blocks were placed end‐to‐end in field‐length strips at eight irrigated maize fields in east central Nebraska in 2016 and 2017. Maize response to N was evaluated with in‐season canopy reflectance measurements and grain yield. Relationships between maize response variables and measured soil and topographic attributes were evaluated and used to delineate MZ. Yield response to N rate was highly variable among and within fields. Soil apparent electrical conductivity had the highest overall correlations with crop response and was used as a clustering variable in five of eight fields. Economic analysis showed a potential advantage to using soil‐based MZ compared to producer‐chosen uniform N rates in five of eight fields. Delineated MZ were able to identify areas with differential soil properties and crop response to N fertilizer. Integrating soil‐based MZ and sensor‐based N management has potential to achieve further economic benefits. Core Ideas: Soil apparent electrical conductivity had the highest correlations to crop response in five of eight fields. Sub‐field economic optimum nitrogen rates exceeded 80 kg N h −1 for six of eight fields. Average economic optimum nitrogen rates ranged from 11 to 96 kg N ha −1 between the two management zones (MZs) for six of eight fields. Variable‐rate nitrogen using soil‐based MZs had higher profit potential in five of eight fields.